Stereoselective synthesis of (+)-isoindolo-beta-carboline - Wakchaure, Prasad B.; Puranik, Vedavati G.; N. P. Argade (Tetrahedron-Asymmetry, 2009)
Starting from homophthalic anhydride and (S)-tryptophan, the stereoselective synthesis of (+)-isoindolo-beta-carboline has been described via the corresponding homophthalimide, its chemoselective oxidative ring contraction, and the intramolecular dehydrative ring closure followed by a geometry-specific demethoxycarbonylation. (C) 2009 Elsevier Ltd. All rights reserved.